Relationship between core muscles, leg arch, hamstring and lumbar flexibility on pop-up ability among surfers - Anak Agung Gede Eka Septian Utama; I Dewa Gd Alit Kamayoga; M. Widnyana; I Putu Yudi Pramana Putra (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Surfing is a sport that requires alternating high, medium, and low intensity at one time. Surfing combines three phases, namely paddling, pop-up, and wave-ride. The surf pop-up phase is characterized by a change from a paddling position to a standing position on the surfboard in one dynamic motion. During this transition, a surfer must move 75% of his body weight in less than one second. Pop-up movement is a unique challenge for the human motor system because it must be done quickly, with sufficient strength, on a moving and unstable surface that requires the readiness of the bio motoric component to avoid injury. This study aimed to see the relationship between core muscles, leg arches, hamstring, and lumbar flexibility on pop-up ability among surfers. Methods: The research uses analytic observational with a cross-sectional approach. The number of samples was 80 people with inclusion criteria, men aged 20-40 years and at least one year of surfing experience. Core muscles were measured using the curl-up test, the footprint test measured leg arches, hamstring flexibility by the sit and reach test, lumbar flexibility by the modified Schober's test, and pop-up ability using the time to pop-up. The research was conducted in Badung regency. Results: This study showed a significant and strong relationship between core muscles (r= 0,57, p-value< 0.001), leg arches (rs= 0.33-0.43, p-values= 0.009 - <0.001), hamstring and lumbar flexibility (rs= 0.31-0.50, p-values= 0.013 - <0.001) on pop-up ability among surfers. Conclusion: There were significant relationships between the core muscles, leg arches, hamstring and lumbar flexibility on pop-up ability among surfers.